Agama dan Kearifan Lokal: Peran Tradisi Bersih Desa Dalam Membangun Hubungan Antar Umat Beragama di Kediri - Arifin, Achmad Zainul (JOM, 2024)
Religion and local wisdom are two inseparable parts. The two are intertwined together in society, influencing each other so that they can exist in society, including the Bersih Desa tradition whose presence penetrates the boundaries of religious space. Bersih Desa tradition in Medowo village exists and is carried out jointly by communities across existing religions, namely Hinduism, Islam and Christianity. This research using a qualitative approach seeks to explain the role of culture in society in building harmonious relationships in a society that is heterogeneous in terms of religion, culture and ethnicity. Research data was taken using interview, observation and documentation techniques. The research results show that first, the Bersih Desa tradition penetrates the boundaries of religious teachings, where this tradition is accepted, implemented and preserved by interfaith communities. Second, the Bersih Desa culture plays its role as a bond between religious communities in Medowo, this role is important in the increasingly complex dynamics of community life challenges in the era of globalization